ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Dian Anggraini; Imron Mawardi (Universitas Airlangga, 2019)
The purpose of this study is to analyze the factors that affect the profitability of Sharia Commercial Bank in Indonesia. The sampling technique used is saturated sampling, so the population and sample is the Sharia Commercial Bank periode October 2014-March 2018 which amounted to 42 months. This study uses a quantitative approach with multiple linear regression analysis technique.The result showed that with 95% confidence level partially variable Financing to Deposit Ratio have significant effect to profitability, while variable Natural Uncertainty Contract Financing, Non Performing Financing, and Equity have no significant effect on profitability of Sharia Commercial Bank in Indonesia. Nevertheless, Natural Uncertainty Contract Financing, Non Performing Financing, Financing to Deposit Ratio and Equity simultaneously have significant effect to the profitability of Sharia Commercial Bank in Indonesia. With the coefficient of determination of 33,2%.Keywords: Natural Uncertainty Contract, Non Performing Financing, Financing to Deposit Ratio, EquityREFFERENCESDepartemen Agama RI.2009. Al-Qur’an dan Terjemahnya hal 546. Bandung: PT Sygma Examedia ArkanleemaHidayah, Liza Nur. 2013. Pengaruh Pembiayaan Natural Uncertainty Contract (NUC) dan Natural Certainty Contract (NCC) Terhadap Profitabilitas Bank Umum Syariah Periode 2008-2012. Skripsi. Malang: Universitas Islam Negeri Maulana Malik Ibrahim.Ikatan Akuntan Indonesia. 2007. Standar Akuntansi Keuangan. Jakarta: Salemba Empat.Kasmir, 2013. Bank dan Lembaga Keuangan Lainnya. Jakarta: PT Raja Grafindo PersadaKurnia, Indra.2012. Analisis Pengaruh BOPO, Equity to Total Assets Ratio, Loan to Assets Ratio, dan Firm Size Terhadap Kinerja Keuangan. Semarang. Universitas Dipone-goroOtoritas Jasa Keuangan. 2017. Laporan Perkembangan Keuangan Syariah. Jakarta: Otoritas Jasa Keuangan. Hlm. 19. 2018. Statistik Perbankan Syariah Tahun 2018. Jakarta: Otoritas Jasa Keuangan. 2017. Statistik Perbankan Syariah Tahun 2017. Jakarta: Otoritas Jasa Keuangan. 2016. Statistik Perbankan Syariah Tahun 2018. Jakarta: Otoritas Jasa Keuangan. 2015. Statistik Perbankan Syariah Tahun 2018. Jakarta: Otoritas Jasa Keuangan. 2014. Statistik Perbankan Syariah Tahun 2018. Jakarta: Otoritas Jasa KeuanganSuryani. 2011. Analisis Pengaruh Financing To Deposit Ratio Terhadap Profitabilitas Perbankan Syariah Di Indonesia. Jurnal Walisongo STAIN Malikus Saleh Lhokseumawe. vol. 19. No. 1 : 48-49.Sutrisno. 2016. The Effects of Financing and Risks on the Performance of Islamic Bank: Empirical evidence from Indonesian Islamic Bank. Business and Management Research Journal Vol. 6 (3): 29-36Taufik, Hidayat. 2011. Buku Pintar Investasi Syariah. Jakarta: Mediakita.Wulandari, Retno. 2017. Pengaruh Capital Adequacy Ratio, Financing to Deposit Ratio, Non Performing Financing, dan Pertumbuhan Dana Pihak Ketiga Terhadap Rteurn On Assets Pada BPRS di Indonesia Periode 2011-2015. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Wasiuzzaman, Shaista dan Hanimas Ayu Bt. Ahmad Tarmizi. 2010. Profitability of Islamic Banks in Malaysia An Empirical Analysis. Journal of Islamic Economics, Banking and Finance, Vol. 6 (4):64